Inflammatory pseudotumor of Castleman disease and IgG4-related disease masquerading as kidney malignancy - Bolong Liu; Yong Huang; Luying Tang; Jiexia Guan; Xiangfu Zhou; Hailun Zhan (BMC, 2021)
Abstract Background With widespread clinical application of imaging techniques, renal space-occupying lesions have been identified at an increasing frequency. Here, we report two rare cases, Castleman disease (CD) and IgG4-related disease (IgG4-RD), presenting primarily with the symptoms and imaging findings of kidney malignancy. Case presentation In case 1, an occupying lesion located in the right renal pelvis was detected using magnetic resonance imaging in a 32-year-old female who presented with hematuria and lumbago. First misdiagnosed as carcinoma of the renal pelvis, the patient underwent right radical nephroureterectomy. However, postoperative pathological and immunohistochemistry studies finally confirmed the diagnosis of CD. In case 2, a 45-year-old male presented with the chief complaint of anuria. Nephrostomy and renal biopsy indicated lymphoma, following which, antegrade urography and computed tomography urography were performed, which revealed bilateral hydronephrosis and mass lesions around the renal pelvis. Partial resection of the masses and frozen section examination indicated the diagnosis of CD. However, the results of postoperative histopathology and immunohistochemistry combined with serum IgG4 were consistent with IgG4-RD. Both the patients recovered well after drug treatment without recurrence of the diseases. Conclusions Inflammatory pseudotumor of CD and IgG4-RD with kidney involvement are primarily diagnosed by postoperative histopathology and can pose a preoperative diagnostic challenge because these lesions can masquerade as kidney malignancy. Therefore, we recommend core biopsy as a nonnegligible procedure to evaluate renal masses and potentially prevent unnecessary surgical treatment.